If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + -2 = 5g Reorder the terms: -2 + 3g = 5g Solving -2 + 3g = 5g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5g' to each side of the equation. -2 + 3g + -5g = 5g + -5g Combine like terms: 3g + -5g = -2g -2 + -2g = 5g + -5g Combine like terms: 5g + -5g = 0 -2 + -2g = 0 Add '2' to each side of the equation. -2 + 2 + -2g = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -2g = 0 + 2 -2g = 0 + 2 Combine like terms: 0 + 2 = 2 -2g = 2 Divide each side by '-2'. g = -1 Simplifying g = -1
| 3(p-1)=3p-2 | | -x+7=2x+13 | | -7w-35=2(w+5) | | X/6=54 | | -x+5=2x-11 | | 5x-12=-2y+3 | | -3/4x-7/8 | | 8(v+7)=-5v-48 | | 3(13-2a)=-13+a | | x-5=-2x+13 | | X+80+2x+20=180 | | X/4-x/12=1/2 | | 10r+15=33-12r-52 | | 5-2x/-3-4-x | | [u-7]=-1/4 | | y-9=4/6(x-3) | | -9y-18=9(y-6) | | 2(a+4)=-3(7x+2)+8x | | -2(x-4)=(3-x) | | 3[-2(x+5)-5]=x+7 | | (y^4)-12*(y^3)+48*(y^2)-145*y+90=0 | | P^4-11p^2+1=0 | | y^4-12y^3+48y^2-145y+90=0 | | 11-15=6x-5-5x | | 3x-6+10=14 | | [-2x]=[8] | | 12=14x-11x | | -3(5-9v)=25+7w | | -8x+5y=131 | | x+47=-72 | | 3x-y=76 | | 3(3+6x)=-81 |